An objective way of locating optimum pitch - NP, Nataraja (Journal of All India Institute of Speech and Hearing, 1972)
Voice may be defined as a laryngeal tone which can be heard or measured. The normal voice should possess certain characteristics of pitch, loudness and quality which make meaning clear, arouse the proper emotional response and ensure a pleasant tonal effect upon the hearer (Berry and Eisenson, 1956). Normal voice may be related to cultural preferences, age and sex as well as social and economic status (Van Riper and Irwin, 1959).